Intussusception in the adult: Review of 17 cases - Villalba Acosta, Joaquín; Redondo Colman, Susana; Vanuno Saragusti, David (Cirugía del Uruguay, 1997)
Intestinal invagination is infrequent in the aduit and generally secondary to tumoral processes. This review intends to analyse presentation features and establish some diagnostic orientation.